PENINGKATAN LITERASI KESEHATAN MENGENAI GERAKAN MASYARAKAT HIDUP SEHAT (GERMAS) MELALUI INOVASI DONGENG BAHAGIA DI KECAMATAN KELAKAR KABUPATEN MUARA ENIM - Siti Halimatul Munawarah; Misnaniarti; Asmaripa Ainy; Haerawati Idris; Rizma Adlia Syakurah; Iwan Stia Budi; Dian Safriantini; Rudy Chendra; Indah Fasha Palingga; Alvera Noviyan (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Currently, Indonesia is facing a triple burden problem, namely the incidence of infectious diseases, increasing cases of non-communicable diseases, and the re-emergence of types of diseases that should have been successfully overcome. It is called the Healthy Living Community Movement (GERMAS) so that everyone is aware, willing, and able to behave healthily. It is essential to introduce school-age children as one of the strategic target groups in developing healthy living behavior from an early age. Methods: The method of this community service activity is carried out by providing education about GERMAS using the innovative BAHAGIA fairy tale media, as well as providing a pre-post test questionnaire to measure changes in the level of knowledge in elementary school age children before and after being given education. Results: Participants in this community service activity were 34 class IV students at SDN 03 Kelekar. There was a significant difference in the respondents' knowledge scores before and after education was carried out using innovative BAHAGIA tales media. Conclusion: Community service activities were attended with great enthusiasm and active participation from all students. It is hoped that GERMAS can be implemented in the school environment more optimally. Keywords: GERMAS; BAHAGIA Tales; Knowledge